China's rapid urban ascent: an examination into the components of urban growth. Issue 1 (2nd January 2018) - Farrell, Kyle; Westlund, Hans
ABSTRACT: Having gone from 11.8% of its population inhabiting urban areas in 1950 to 49.2% by 2010, China represents the most dramatic urban transformation the world has seen. With the contemporary urban narrative presenting new challenges, particularly in terms of its unprecedented pace and scale, this paper conducts an inquiry into the nature and causes of China's rapid urban ascent. Making use of a new analytical framework, this paper maps out the changing stages of China's urban transition and examines the components of urban growth underpinning it. It arrives at several notable findings. Rural to urban migration has been the dominant component of urban growth, followed by urban natural population increase and reclassification. Although China's urban growth rates were high, it is the reduction in rural growth rates that underpinned China's particularly rapid urbanization rates. China is currently in the latter part of the accelerated stage of its urban transition, and is expected to enter the terminal stage by 2030. In light of China's ongoing urban transition, this paper concludes with reflections on China's New-Type Urbanization Plan 2014–2020 .